Molecular genetic identification of Wuzhishan ant chicken, a newly discovered resource in China - Gu, Lihong; Wu, Fanghu; Zheng, Xinli; Zhang, Xiaohui; Chen, Yanmin; Lu, Lizhi; Liu, Xiangxiang; Mo, Shuhui; Chao, Zhe; He, Zhongchun; Shang, Yuanyuan; Wei, Dong; et al. (Frontiers in Veterinary Science, 2024)
The Wuzhishan ant (MY) chicken exhibits significant differences compared with other chicken breeds. However, the molecular genetic relationship between the MY breed and other chicken breeds has not been assessed to date. Whole-genome resequencing was used to compare genetic diversity, nucleotide diversity, the fixation index, the linkage disequilibrium coefficient, and phylogenetic tree relationships between the MY breed and the Wenchang (WC), Danzhou (DZ), Bawangling (BW), and Longshengfeng (LF) breeds. A total of 21,586,378 single nucleotide polymorphisms and 4,253,341 insertions/deletions were screened out among the five breeds. The MY breed had the second-highest genomic genetic diversity and nucleotide diversity and the lowest LD coefficient among the five breeds. Moreover, phylogenetic tree analysis showed that individual birds of each breed clustered together with those of their respective breeds. Our data indicated that the MY breed is distinct from the other breeds and can be considered a new genetic resource.